2006
DOI: 10.1590/s0104-42302006000600016
|View full text |Cite
|
Sign up to set email alerts
|

Efetividade do tratamento de gestantes hipertensas

Abstract: Introduction of an antihypertensive therapy during gestation was of fundamental importance for health improvement and pressure control of the pregnant woman with HSP. Nevertheless, it has been of little help for prevention of perinatal intercurrences. This was substantiated by the absence of improvement in the gestational conditions between the treated group when compared to the non-treated. Medication did not significantly improve the maternal-fetal blood flow and consequently in the birth condition of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
2
19

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 9 publications
1
7
2
19
Order By: Relevance
“…Similar prevalences of HSP were observed in other studies conducted in tertiary care hospitals 9,14,15 . However, lower values were found in other reports 10,11,[16][17][18][19] . Two studies conducted in Brazil 17,18 and another conducted in India 10 also found higher prevalences of PE.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Similar prevalences of HSP were observed in other studies conducted in tertiary care hospitals 9,14,15 . However, lower values were found in other reports 10,11,[16][17][18][19] . Two studies conducted in Brazil 17,18 and another conducted in India 10 also found higher prevalences of PE.…”
Section: Discussioncontrasting
confidence: 57%
“…However, lower values were found in other reports 10,11,[16][17][18][19] . Two studies conducted in Brazil 17,18 and another conducted in India 10 also found higher prevalences of PE. However, other studies found higher prevalences of chronic hypertension 15,16,20,21 .…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…A a-metil-dopa é um dos anti-hipertensivos mais utilizados pelas gestantes e tem como objetivo evitar as complicações decorrentes de síndromes hipertensivas como a prematuridade e morbi-mortalidade perinatal devido à hipoxia intra-uterina 41,42 .…”
Section: Discussionunclassified